2019
DOI: 10.1101/660860
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increase in ribosomal proteins activity: Translational reprogramming inVanilla planifoliaJacks., againstFusariuminfection

Abstract: BackgroundUpon exposure to unfavorable environmental conditions, plants need to respond quickly to maintain their homeostasis. For instance, physiological, biochemical and transcriptomical changes must occur during interactions with pathogens, this causing the triggering of pathogen- and plant-derived molecules. In the case of Vanilla planifolia Jacks., a worldwide economically important crop, it is susceptible to Fusarium oxysporum f. sp. vanillae. This pathogen causes root and stem rot in vanilla plants that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…One that is probably less commonly thought of is the role ribosomal proteins have in post-transcriptional and translational regulation [55][56][57]. The differential expression of specific ribosomal proteins in response to abiotic and biotic stress has been previously reported [55,56,58,59]. Interestingly, in this study, ribosomal proteins were more highly represented in the up-regulated (41 up-regulated, nine downregulated) DEGs.…”
Section: Genes Differentially Expressed In Transgenic Lines Compared supporting
confidence: 48%
“…One that is probably less commonly thought of is the role ribosomal proteins have in post-transcriptional and translational regulation [55][56][57]. The differential expression of specific ribosomal proteins in response to abiotic and biotic stress has been previously reported [55,56,58,59]. Interestingly, in this study, ribosomal proteins were more highly represented in the up-regulated (41 up-regulated, nine downregulated) DEGs.…”
Section: Genes Differentially Expressed In Transgenic Lines Compared supporting
confidence: 48%
“…The 40S ribosomal protein S4 (Manes.03G095200) had ratios of 1.59 in T200 and −1.06 in TME3. An increase in transcript levels of this protein was observed in Vanilla planifolia Jacks infected with fungi [ 51 ], whereas there was a decrease in transcript in Arabidopsis 48 h after inoculation with A. tumefaciens [ 52 ]. The 60S ribosomal protein L13 (Manes.07G017100) was under-expressed in T200 (−3.86) and over-expressed in TME3 (2.11).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the ribosomal proteins with decreased abundance in the nucleus under flg22 and nlp20 compared to control (nine proteins) have a repressed function in the nucleus during the Arabidopsis immune response. In a previous study the ribosomal protein transcripts were investigated in Vanilla planifolia when infected with Fusarium oxysporum ( Solano de la Cruz et al, 2019 ). Seven ribosomal proteins that showed an increase in abundance in the nucleus after elicited immunity in our study also showed an increase in their transcript expression patterns in Vanilla after 2days of Fusarium infection.…”
Section: Discussionmentioning
confidence: 99%